Construction of Islamic education in the contemporary era: an analytical study related to the challenges of modernity of Islamic education - Gafarurrozi, Muhammad; Rohman, Moh. Fatkur (LPPM Universitas Ibn Khaldun, Bogor, 2025)
The current of modernization has entered the industrial era 4.0 and 5.0. Various paradigms of progress in the fields of science and technology have entered Indonesia massively. Modernization also has a very large influence on the world. The modernization that is currently happening has a variety of impacts on people's lives. Changes in lifestyle, shifting paradigms of life, to socio-cultural influences from abroad, increasingly provide a complex picture of the development of modernization in Indonesia. The purpose of the study is to analyze the challenges of modern Islamic education in the contemporary era. The research method uses a qualitative approach, with the type of library research. The results of the study show that Islamic education must respond to the challenges of modernity that are currently developing by abandoning old scientific paradigms, which only give rise to the decline of Islamic education studies. Having an open attitude to the flow of modernization, conducting cross-reference studies, between scientific fields, will create a space for new formulations in understanding the revitalization of Islamic education. So that the current formulation of Islamic education is able to answer various kinds of problems and challenges that arise from the flow of modernization.